2015
DOI: 10.4172/2157-7579.1000272
|View full text |Cite
|
Sign up to set email alerts
|

Gross and Microanatomical Studies on the Uterus of Japanese Quail (Coturnix japonica) During the Post-hatching Period with Special Emphasis on Sperm Host Gland

Abstract: The quail acts as a model for recent experimental studies and its oviduct development is of special interest. This study was carried out on 61 adult female Japanese Quail (Coturnix japonica) collected from quail farms in Assiut and South Valley Universities in order to characterize the morphological features of the uterus during the post-hatching life. The process of development was consisted of three stages: undifferentiated, differentiated and adult stage. The undifferentiated stage began from day of hatchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…At higher magnification the surface of lining cells were seen having microvillus projections. Ibrahim et al (2015) studied utero-vaginal junction of Japanese quail and showed transition of mucosal folds from longitudinal folds of uterus to complex interconnecting folds of the vagina. The mucous membrane of this area was covered densely with cilia.…”
Section: Resultsmentioning
confidence: 99%
“…At higher magnification the surface of lining cells were seen having microvillus projections. Ibrahim et al (2015) studied utero-vaginal junction of Japanese quail and showed transition of mucosal folds from longitudinal folds of uterus to complex interconnecting folds of the vagina. The mucous membrane of this area was covered densely with cilia.…”
Section: Resultsmentioning
confidence: 99%